Flexural strength of a composite resin light cured with different exposure modes and immersed in ethanol or distilled water media - dos Santos, Saulo Galvão (Medknow Publications & Media Pvt Ltd, 2012)
AIM: The aim of this in vitro study was to evaluate the flexural strength of a composite resin polymerized with three different modes of light exposure. MATERIALS AND METHODS: The three different modes of light exposure were conventional, 600 mW/cm2/40s; soft start, 300 mW/cm2/10s + 600 mW/cm2/30s; pulse delay, 600 mW/cm2/1s + 60 s of waiting time + 600 mW/cm2/39s). Twenty samples were prepared for each polymerization method. Flexural strength (FS) tests were carried out with a 2 kN load at a speed of 0.5 mm/ min. All tested groups were submitted to analysis of variance (one-way-ANOVA) and Tukey's test (P < 0.05). RESULTS: When stored in water, conventional and pulse delay groups presented higher FS values which were statistically different from the soft start group. When stored in 100% ethanol, conventional and soft start groups presented higher FS values which were statistically different from the pulse delay group. CONCLUSION: Different polymerization modes and immersion media can affect the physical properties (flexural strength) of composite resin.